Overcoming male factor infertility with intracytoplasmic sperm injection - Borges Jr.,Edson (2017)
Summary Objective: To evaluate the effect of male factor infertility on intracytoplasmic sperm injection (ICSI) outcomes compared with a control group presenting isolated tubal factor. Method: This retrospective study included 743 couples undergoing ICSI as a result of isolated male factor and a control group consisting of 179 couples undergoing ICSI as a result of isolated tubal factor, performed in a private university- -affiliated in vitro fertilization center, between January/2010 and December/2016. Patients were divided into two groups according to maternal age: women ≤35 years old and >35 years old. The effects of infertility causes on laboratorial and clinical ICSI outcomes were evaluated using Student's t-test and (2 test. Results: No differences in controlled ovarian stimulation outcomes were observed between male factor cycles and tubal factor cycles in the two age groups. Implantation (male factor 35.5% vs. tubal factor 32.0%, p=0.340), pregnancy (male factor 46.9% vs. tubal factor 40.9%, p=0.184) and miscarriage (male factor 10.3% vs. tubal factor 10.6%, p=0.572) rates were similar between the infertility groups, irrespective of female age. Considering maternal age, the cancelation rate was higher in older women (>35 years old) undergoing ICSI as a result of male factor infertility (17.4% vs. 8.9%, p=0.013). Conclusion: Our results showed that there is no difference in the outcomes of pregnancy between couples with male or tubal factor infertility, which indicates that ICSI surpasses the worse specific outcomes associated with male factor.